2012
DOI: 10.1155/2012/631856
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Koala Scat Persistence and Detectability with Implications for Pellet-Based Fauna Census

Abstract: Establishing species distribution and population trends are basic requirements in conservation biology, yet acquiring this fundamental information is often difficult. Indirect survey methods that rely on fecal pellets (scats) can overcome some difficulties but present their own challenges. In particular, variation in scat detectability and decay rate can introduce biases. We studied how vegetation communities affect the detectability and decay rate of scats as exemplified by koalas Phascolarctos cinereus: scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…With the detection dog off-leash, the accuracy reached 100%. Comparing the detection dog results to a previous study on human survey scat detection11 revealed that in an experimental setting, the dog was as accurate but much more efficient than a human being (Table 4). In fact the detection dog was on average 350 times quicker.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…With the detection dog off-leash, the accuracy reached 100%. Comparing the detection dog results to a previous study on human survey scat detection11 revealed that in an experimental setting, the dog was as accurate but much more efficient than a human being (Table 4). In fact the detection dog was on average 350 times quicker.…”
Section: Discussionmentioning
confidence: 72%
“…In fact the detection dog was on average 350 times quicker. This comparison has some limitations, as the previously mentioned experimental survey11 was extremely thorough (up to 49 minutes for a 5 m 2 plot), whereas consultancy projects would be more limited by working within budget constraints which undoubtedly limits search time. In order to test the performance of the detection dog in a more realistic field survey, we compared its performance to that of a human-only team under a commonly used scat survey method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations